Some Results of Conditionally Sequential Absorbing Maps in 2-Menger Space - Srinivas, V.; Satyanna, K. (Communications in Mathematics and Applications, 2022)
This paper aims to present two results in probabilistic 2-metric space by using the concepts of conditionally sequential absorbing maps and reciprocally continuous mappings. These are generalizations of the theorem proved by Gupta et al. [5]. Further, these are justified by supporting examples.